(untitled) (Papeles, 2024)
This paper is the result of both research and university extension projects, where agroecological transition has been the central focus of our inquiry and engagement with the local community. To this end, we have drawn on the theoretical framework of Fundamental Human Needs developed by Manfred Max-Neef and his collaborators. We employed a transdisciplinary methodology to construct knowledge collectively, thus fostering a dialogue of knowledge between academics and small-scale farmers. Specifically, in this paper we develop a more theoretical reflection on agroecology as a synergistic and human-scale mode of production, one that respects planetary boundaries and fulfills Fundamental Human Needs